America as an Ordinary Country : U.S. Foreign Policy and the Future - Rosecrance, Richard (Cornell University Press, 2019)
If the possibilities for peace are to be increased in the next generation, America should change its role in world affairs from dominant superpower to ordinary country.That is the conclusion reached by ten distinguished specialists, five of them writing from abroad, as they reflect on recent U.S. foreign policy and survey its prospects. Ranging over crucial issues in military affairs, in the political sphere, and in the field of economics, their essays point out errors and misjudgments of the past and offer realistic, thought-provoking recommendations for the future.